2015
DOI: 10.1016/j.tsf.2015.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of hydrogenated amorphous silicon germanium thin films and solar cells deposited by hot wire chemical vapor deposition

Abstract: Optimization of hydrogenated amorphous silicon germanium thin films and solar cells deposited by hot wire chemical vapor deposition, Thin Solid Films (2015), ABSTRACTThis work studies hydrogenated amorphous silicon germanium films, deposited by hot wire chemical vapor deposition, to be used as low band gap absorber material in thin film solar cells. Material properties, such as the bonding configurations, the ambipolar diffusion length and the optical band gap, were examined as a function of the substrate temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 14 publications
4
23
0
Order By: Relevance
“…The need of heterostructures is inherent in these systems to provide efficient charge carrier extraction. Thus, s-shaped I-V curves have been frequently observed in CdTe [6], [58], [59], copper indium (gallium) selenide [CI(G)S] [60]- [62], and a-Si cells [63]- [65].…”
Section: S-shaped I-v Characteristics In Thin-film Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The need of heterostructures is inherent in these systems to provide efficient charge carrier extraction. Thus, s-shaped I-V curves have been frequently observed in CdTe [6], [58], [59], copper indium (gallium) selenide [CI(G)S] [60]- [62], and a-Si cells [63]- [65].…”
Section: S-shaped I-v Characteristics In Thin-film Solar Cellsmentioning
confidence: 99%
“…Accordingly, solar photovoltaics research has been focusing on the usage of a-Si not as the absorbing material, but rather as passivated contact materials, as described in detail above. However, studies that report s-shaped I-V curves in solar cells with a-Si absorber also found the barriers between absorber and charge transport layers to be the culprit [63]- [65], [85].…”
Section: Amorphous Silicon Solar Cellsmentioning
confidence: 99%
“…To achieve this, we have utilized intrinsic layers of hydrogenated amorphous silicon (a-Si:H) and silicon germanium (a-SiGe:H) for the top, middle, and bottom cells, and hot wire chemical vapor deposition (HWCVD) as the fabrication technique. HWCVD allows for the fabrication of high quality low-band gap a-SiGe:H 5,6 and for conformal deposition at high rates. 7,8 HWCVD can contribute to an additional reduction of costs/ Wp compared to plasma enhanced chemical vapor deposition (PECVD), due to lower system and operating expenses as well as its excellent compatibility with roll to roll fabrication.…”
mentioning
confidence: 99%
“…Detailed descriptions of the vacuum system and the HWCVD deposition process are given elsewhere. 6,10 Figure 1 shows the refractive indices and the absorption coefficients of three types of absorber materials with different Ge fraction (x ¼ Ge=½Si þ Ge ). The optical constants were obtained from reflection and transmission measurements of individual layers on Corning EAGLE XG V R glass that were fitted using the density-of-states model of O'Leary, Johnson, and Lim.…”
mentioning
confidence: 99%
See 1 more Smart Citation